(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
The purpose of this study is to analyze the impact of e-filing and digital literacy on MSME taxpayer compliance in Karanganyar Regency. The research hypothesis states that e-filing and digital literacy positively impact MSME taxpayer compliance in Karanganyar Regency. Sampling was conducted using an accidental sampling method, where respondents were selected based on who the MSME actors were coincidentally encountered by the researcher in the field. The data source in this study used a questionnaire distributed to MSME actors in Karanganyar Regency. The type of data used in this study was primary data. The results of the analysis obtained t there is no significant effect of simultaneous e-filing implementation on MSME taxpayer compliance in Karanganyar Regency. The results of the analysis obtained t there is no influence of digital literacy simultaneously on MSME taxpayer compliance in Karanganyar Regency. The results of the F test analysis show an insignificant effect of simultaneous E-Filing and digital literacy implementation on MSME taxpayer compliance in Karanganyar Regency. The calculation results obtained an R2 value = 0.002 = 2% meaning that the small influence given by the implementation of e-filing and digital literacy on MSME taxpayer compliance in Karanganyar Regency.